Oral microbiota related to allergy in Norwegian adults - Mikyeong Lee, PhD; Hilde Kristin Vindenes, MD, PhD; Farnaz Fouladi, PhD; Rajesh Shigdel, PhD; James M. Ward, MSc; Shayamal D. Peddada, PhD; Stephanie J. London, MD, DrPH; Randi Jacobsen Bertelsen, PhD (Journal of Allergy and Clinical Immunology: Global)
Background: Oral microbiome composition has been linked to onset and progression of several localized and systemic diseases. Associations with allergy in adults have been less explored. Objective: We sought to identify oral microbiota associated with allergy outcomes in adults using high-throughput sequencing data. Methods: We characterized bacterial communities of gingival samples from 453 Norwegian adults (average age, 28 years) using 16S rRNA gene amplicon sequencing. We examined more than 2200 bacterial taxa in relation to self-reported current asthma, eczema, or rhinitis, and seroatopy (IgE > 0.70 kU/L). We used linear regression to determine whether overall bacterial diversity differed by each allergic outcome and analysis of composition of microbiomes with bias correction (ANCOM-BC2) to identify differentially abundant taxa. Results: Less diverse oral bacterial communities were observed (P < .05) in individuals with atopy or rhinitis compared with those without. Bacterial diversity did not differ by asthma and eczema status. While no bacterial taxa were differentially abundant by asthma, many were differentially abundant (P < .05 after multiple-testing correction) in relation to atopy, eczema, and rhinitis. These taxa include several from the genera Leptotrichia and Fusobacterium. Some, including Streptococcus, were previously implicated in respiratory health, whereas others were novel. We also found taxa related to nasal medication use in individuals with rhinitis. Notably, microbial network interconnections differed by allergy status. Conclusions: Bacterial community compositions of oral gingival samples may play a role in allergic outcomes in adults. These findings could contribute to the development of novel treatment strategies.